Using a testis regeneration model, FGF9, LIF, and SCF improve testis cord formation while RA enhances gonocyte survival - Awang-Junaidi, Awang Hazmi; Fayaz, Mohammad Amin; Goldstein, Savannah; Honaramooz, Ali (Springer, 2022)
Implantation of testis cell aggregates from various donors under the back skin of recipient mice results in de novo formation of testis tissue. We used this implantation model to study the putative in vivo effects of six different growth factors on testis cord development. Recipient mice (n = 7/group) were implanted with eight neonatal porcine testis cell aggregates that were first exposed to a designated growth factor: FGF2 at 1 µg/mL, FGF9 at 5 µg/mL, VEGF at 3.5 µg/mL, LIF at 5 µg/mL, SCF at 3.5 µg/mL, retinoic acid (RA) at 3.5 × 10-5 M, or no growth factors (control). The newly developed seminiferous cords (SC) were classified based on their morphology into regular, irregular, enlarged, or aberrant. Certain treatments enhanced implant weight (LIF), implant cross-sectional area (SCF) or the relative cross-sectional area covered by SC within implants (FGF2). RA promoted the formation of enlarged SC and FGF2 led to the highest ratio of regular SC and the lowest ratio of aberrant SC. Rete testis-like structures appeared earlier in implants treated with FGF2, FGF9, or LIF. These results show that even brief pre-implantation exposure of testis cells to these growth factors can have profound effects on morphogenesis of testis cords using this implantation model.